2020
DOI: 10.1007/s43188-020-00063-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of Centella asiatica 50% ethanol extract against acetaminophen-induced acute liver injury in BALB/c mice

Abstract: N-acetyl-p-aminophenol (acetaminophen, APAP) is a well-known component of analgesic and antipyretic monotherapy products. However, exceeding the recommended dose can lead to serious injury to the liver. We conducted this study to determine the potential of Centella asiatica as a natural substance to protect against APAP-induced liver injury. When acute hepatotoxicity was induced in mice by APAP overdose, their liver weight decreased significantly (p < 0.05). However, mice treated with C. asiatica 50% ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The antioxidant and anti‐inflammatory actions were identified to be due to the asiaticoside content present in the extract. Hence, asiaticoside is an effective phytochemical in protecting against APAP‐induced liver injury 107 …”
Section: Other Organ‐protective Effects Of Asiaticoside and Madecasso...mentioning
confidence: 99%
“…The antioxidant and anti‐inflammatory actions were identified to be due to the asiaticoside content present in the extract. Hence, asiaticoside is an effective phytochemical in protecting against APAP‐induced liver injury 107 …”
Section: Other Organ‐protective Effects Of Asiaticoside and Madecasso...mentioning
confidence: 99%
“…Some reports have also depicted the strong correlation between total phenols and antioxidant activity (Baskaret al, 2011). Oxidative stress generated during paracetamol toxicity causing hepatic injury can be prevented which can be attributed to antioxidant activity of phenolic compound (Wu et al, 2017) Paracetamol, used as antipyretic has been known to cause liver toxicity when in excessive overdose (Park et al, 2021). Paracetamol when in above the therapeutic level, exerts toxicity by the activity of hepatocytes metabolizing paracetamol through microsomal cytochrome P450 (CYP450) into toxic byproducts.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other studies, we found that the radical scavenging activity of VCEC was significantly greater and exhibited higher, dose-dependent, free radical scavenging capacity than antioxidant positive control vitamin C and VE or CE alone. Several studies have found that VE and CE have potential hepatoprotective activity against CCl 4 and ethanol-induced liver toxicity [11,[30][31][32][33]. However, more research is needed to fully understand why the combination of the two extracts has synergistic effects in reducing liver damage compared to using either extract alone.…”
Section: Discussionmentioning
confidence: 99%